The effect of progressive muscle relaxation technique and myofascial release technique on premenstrual symptoms, blood circulation, and quality of life in women with premenstrual syndrome: A single-blind randomized controlled study - Ovgun, Cisel Demiralp; Tuzun, Emine Handan (Lippincott Williams & Wilkins, 2023)
Background:Premenstrual syndrome (PMS) is a common condition in women of reproductive age. It is characterized by a range of behavioral, physical, and psychological symptoms. The aim of this study is to investigate the effects of progressive relaxation and myofascial release technique (MRT) on premenstrual symptoms, blood flow rate, pain, sleep quality and quality of life, in women with PMS. Method:The study will conduct as a single-blind randomized controlled trial. Study registered at the ClinicalTrial.gov Protocol ID: NCT05836454. The volunteers will be randomized using allocation software to be divided into 3 groups: the progressive muscle relaxation group, the MRT group, and the control group. Assessments will be conducted by another physical therapist who is blinded to the groups. The assessments will include the Premenstrual Syndrome Severity Score, Blood Flow Measurements, Short Form McGill Pain Questionnaire, the Pittsburgh Sleep Quality Index and Short Form-36 Health Survey. Discussion:Since both methods provide relaxation, improve symptoms and quality of life, they have not been compared to each other in the literature. This prompt to us to plan this study.
Keywords: myofascial release therapy; premenstrual syndrome; progressive relaxation